Pandangan Non-Government Organization (NGO) Perempuan tentang Fenomena Childfree dalam Perspektif Hukum Keluarga Islam: Studi pada LSM Damar dan PKBI Lampung - Aulia Lutfiani; Abdul Qodir Zaelani; Ahmad Burhanuddin (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the perspectives of women’s non-governmental organizations, namely Damar Foundation and PKBI Lampung, regarding the childfree phenomenon that has emerged in modern society and is considered contrary to the principles of Islamic family law, particularly concerning the purpose of marriage, lineage preservation (hifz al-nasl), and reproductive responsibilities within the family. The childfree phenomenon reflects changing perspectives among younger generations regarding the meaning of marriage, raising legal issues concerning its compatibility with Islamic legal norms in Indonesia. This study employs an empirical research method with a case approach. The findings indicate that both organizations perceive childfree as a social phenomenon that should be understood contextually. Damar Foundation emphasizes gender justice and women’s reproductive rights, while PKBI Lampung highlights reproductive health, public welfare (maslahah), and mutual consultation between spouses. This study contributes to the development of Islamic family law that is more responsive to contemporary social dynamics.